2019
DOI: 10.1186/s13293-019-0220-3
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ modulates energy homeostasis through inhibition of neurotransmission at VMN SF-1/ARC POMC synapses in a sex- and diet-dependent manner

Abstract: BackgroundOrphanin FQ (aka nociceptin; N/OFQ) binds to its nociceptin opioid peptide (NOP) receptor expressed in proopiomelanocortin (POMC) neurons within the arcuate nucleus (ARC), a critical anorexigenic component of the hypothalamic energy balance circuitry. It inhibits POMC neurons by modifying neuronal excitability both pre- and postsynaptically. We tested the hypothesis that N/OFQ inhibits neurotransmission at synapses involving steroidogenic factor (SF)-1 neurons in the ventromedial nucleus (VMN) and AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 62 publications
1
37
1
Order By: Relevance
“…The findings of an anorexigenic effect on activation of nociceptin-expressing neurons might seem at odds with the previous literature that describes an increase in feeding when pharmacological doses of nociceptin are delivered either intracerebroventricularly or into specific brain regions such as the arcuate nucleus (20, 28, 51). It has been suggested that this orexigenic effect occurs via inhibition of arcuate POMC and VMH neurons (26, 28, 29). However, injection of neuropeptides is unlikely to resemble the spatial and temporal pattern of physiological release but will instead likely induce long-lasting binding to nociceptin receptors throughout the arcuate nucleus, VMH, and other regions.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The findings of an anorexigenic effect on activation of nociceptin-expressing neurons might seem at odds with the previous literature that describes an increase in feeding when pharmacological doses of nociceptin are delivered either intracerebroventricularly or into specific brain regions such as the arcuate nucleus (20, 28, 51). It has been suggested that this orexigenic effect occurs via inhibition of arcuate POMC and VMH neurons (26, 28, 29). However, injection of neuropeptides is unlikely to resemble the spatial and temporal pattern of physiological release but will instead likely induce long-lasting binding to nociceptin receptors throughout the arcuate nucleus, VMH, and other regions.…”
Section: Discussioncontrasting
confidence: 82%
“…These data therefore suggested the possibility that nociceptin, released from aBNST neurons (that perhaps coexpress GABA), inhibits arcuate AgRP/NPY neurons to suppress feeding. However, nociceptin-expressing cells are also found in the ventromedial hypothalamus (VMH), and injection of nociceptin agonists to this brain region increases feeding (28, 29). Therefore, we next investigated whether VMH neurons, which may express and release endogenous nociceptin in the arcuate nucleus, directly synapse with arcuate NPY neurons.…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrate that E 2 enhances excitatory neurotransmission at VMN PACAP/ARC POMC synapses via activation of G q -coupled mERs. We and others have shown previously that long-term exposure to HFD produces central insulin resistance that is sexually differentiated and associated with attenuated anorexigenic signaling within VMN SF-1/ARC POMC synapses [37][38][39]. We therefore wanted to examine whether a similar duration of HFD exposure could dampen anorexigenic transmission at VMN PACAP/ARC POMC synapses.…”
Section: Experiments 1: In Vitro Effects Of Exogenous Pacap On the Excmentioning
confidence: 99%
“…The role of GIRK for hyperpolarization effect of N/OFQ is further supported by findings that N/OFQ-induced outward potassium currents in the arcuate nucleus and ventromedial nucleus of the hypothalamus are suppressed by tertiapin [35] and SKH23390 [36], both of which are known as selective GIRK inhibitors. Outward K + currents through GIRK have been demonstrated in many brain areas including ventromedial nucleus of hypothalamic nucleus [36], arcuate nucleus [3738], perifornical and lateral areas of tuberal hypothalamus [39], hippocampal pyramidal neurons [33], lateral and central amygdala [34], thalamic reticular nucleus (NRT), and ventrobasal complex [40]. GIRK activation by N/OFQ in these brain areas hyperpolarizes neurons and thus inhibits neuronal excitability.…”
Section: Electrophysiological Effects Of N/ofqmentioning
confidence: 99%